A repercussão pública da participação do Brasil na Minustah (2004-2011) - Gonçalves, Israel Aparecido (Universidade Federal de São Carlos, 2012)
The object of this work is to analyze the public impact of Brazil's participation in the MINUSTAH - United Nations Stabilization Mission in Haiti. To understand the public impact we have studied three fields: academe, Congress and the written press in Brazil. The methodology of this study was guided by intensive reading of essays and papers about the Brazilian participation in MINUSTAH and analysis of primary sources, such as laws and official documents. The results show there is a positive public image of the Brazilian participation in MINUSTAH, even with some critical periods.
Keywords: Ciência política; Brasil - congresso; Política externa; Mídia impressa; Minustah; Congresso Nacional; Minustah; National Congress; media brazilian; CIENCIAS HUMANAS::CIENCIA POLITICA